ANALISIS SEMANTIK AWZANIL FI'IL DALAM SURAT AL-‘ALAQ: PENDEKATAN LINGUISTIK - Rissa Rahmadaniati (Jurnal Sathar, 2025)
This study aims to analyze the forms of verbs in QS Al-‘Alaq using Arabic semantic and linguistic approaches. The focus of the study is directed at expressing meaning through the patterns of verbs (awzān al-fi‘il) used in this letter. QS Al-‘Alaq as the first revelation is very interesting to study because almost all of its verses use the structure of the number of verbs (verbal sentences), which reflect the dynamics of Islamic preaching messages and spirituality. This study uses a qualitative method with a literature study type. The primary data is the text of QS Al-‘Alaq, while the secondary data comes from classical and modern Arabic interpretation and linguistic literature. The analysis technique is carried out descriptively-analytical by studying the form of verbs, determining its wazan, and analyzing its meaning from a semantic perspective. The results of the study show that the verbs in QS Al-‘Alaq use various patterns such as fa‘ala, fa‘‘ala, istaf‘ala, and iftā‘ala, each of which has a certain nuance of meaning. The meaning relations found include synonymy, polysemy, and hyponymy. Theologically, the use of these verbs strengthens the message of revelation about the importance of knowledge, a warning against human arrogance, and an invitation to draw closer to Allah. This study confirms that the verb forms in the Qur'an are not only grammatical structures, but also a means of conveying deep spiritual meaning.